Constraints on the upper crustal magma reservoir beneath Yellowstone Caldera inferred from lake‐seiche induced strain observations. Issue 3 (13th February 2013) - Luttrell, Karen; Mencin, David; Francis, Olivier; Hurwitz, Shaul
<x xml:space="preserve">Abstract</x> [1] Seiche waves in Yellowstone Lake with a ~78‐minute period and heights <10 cm act as a load on the solid earth observed by borehole strainmeters with subnanostrain sensitivity throughout the Yellowstone Caldera. The far‐field strain induced by the load of the seiche waves calculated with a homogeneous elastic model representing the upper crust is more than an order of magnitude smaller than the measured strain amplitude ~30 km from the lake shore. By contrast, the observed far field strain amplitudes are consistent with the seiche load on a two‐layered viscoelastic model representing an elastic upper crust overlying a partially molten body deeper than 3–6 km with Maxwell viscosity less than 1011 Pa s. These strain observations and models provide independent evidence for the presence of partially molten material in the upper crust, consistent with seismic tomography studies that inferred 10%–30% melt fraction in the upper crust.